2017
DOI: 10.1007/s00268-017-4173-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Abdominal Wall Hernias and Repair on Patient Quality of Life

Abstract: VHR can improve 1-year postsurgical AW-QOL to levels similar to that of the general population. The MCID of the modified AAS is 7.6 points. Patients with high baseline scores should be counseled about the lack of potential benefit in QOL from elective VHR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 25 publications
0
18
0
1
Order By: Relevance
“…Survey responses are normalized to a scale ranging from 1 (poor) to 100 (perfect), with normal abdominal wall quality of life being 80 or greater. The minimal clinically important difference is 7 for a minor change and 14 for a major change 910. Preoperative pain scores were assessed with a visual analog scale ranging from 0 (no pain) to 10 (worst possible pain); the minimal clinically important difference is 1 11…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Survey responses are normalized to a scale ranging from 1 (poor) to 100 (perfect), with normal abdominal wall quality of life being 80 or greater. The minimal clinically important difference is 7 for a minor change and 14 for a major change 910. Preoperative pain scores were assessed with a visual analog scale ranging from 0 (no pain) to 10 (worst possible pain); the minimal clinically important difference is 1 11…”
Section: Methodsmentioning
confidence: 99%
“…The minimal clinically important difference is 7 for a minor change and 14 for a major change. 9 10 Preoperative pain scores were assessed with a visual analog scale ranging from 0 (no pain) to 10 (worst possible pain); the minimal clinically important difference is 1. 11 …”
Section: Methodsmentioning
confidence: 99%
“…A generic validated QOL scale should be more acceptable to population and observers and should be consistent and acceptable in both short and long term follow up. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] Literature review has showed that, it is best to use a generic scale with a disease specific scale along with a validated pain scale that can cover the immediate postoperative period. 8,13,14 Pain scores should be used in the peri-operative period to determine if patient has developed any acute pain or his pre-operative pain is continuing and becoming a chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Time frame for follow up is the most diverged subject in the literature, where quality of life was measured as soon as next day of surgery to up to five years. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] No consistency was found in the follow up period and in different studies it ranges from days to years. Literature review also did not help to conclude the best time for follow up.…”
Section: Discussionmentioning
confidence: 99%
“…It was only used for QOL assessment in two of the included studies, both in the last 5 years. Cherla et al [ 17 ] assessed QOL using AAS in patients with AHW undergoing reconstruction.…”
Section: Quality-of-life Assessment Toolsmentioning
confidence: 99%